Exploring a Novel Hypothesis: Could the Eye Function as a Radar or Ultrasound Device in Depth and Distance Perception? Neurophysiological Insights - Hüseyin Findik; Muhammet Kaim; Feyzahan Uzun; Ayhan Kanat; Osman Nuri Keleş; Mehmet Dumlu Aydin (Life)
Recent advancements in ocular physiology suggest that the eyes may function similarly to radar antennae or ultrasound probes, with the occipital cortex acting as a detector, challenging the traditional view of binocular vision as the primary mechanism for depth and distance perception. Methods: We conducted a comprehensive analysis of the neuroanatomical and histological architecture of the neuro-optico-cortical systems in a male wild rabbit model. The objective was to identify potential structural and functional similarities between the retino-optical system and radar/ultrasound effector-detector systems. Results: Histological examination revealed significant similarities between retinal morphology and radar/ultrasound systems. The outermost retinal layer resembled an acoustic lens, with underlying layers functioning as acoustic matching layers. The ganglion cell layer exhibited characteristics akin to the piezoelectric elements of transducers. Conclusions: Our findings support the hypothesis that the retinal apparatus functions similarly to radar antennae or ultrasound probes. Light-stimulated retinal-occipital cortex cells perceive objects and emit electromagnetic waves through the retina, which are reflected by objects and processed in the occipital cortex to provide information on their distance, shape, and depth. This mechanism may complement binocular vision and enhance depth and distance perception in the visual system. These results open new avenues for research in visual neuroscience and could have implications for understanding various visual phenomena and disorders.